Habitações populares construídas com placas cimentícias com adições de borracha de pneus - Köhler, Ana Lúcia (2010)
A popular habitation must be understood not only as a simple habitation unit but also as a comfortable, safe and salubrious space. Therefore it is necessary a study regarding the use of alternative materials, as well as the more indicated architectonic typologies. Rubber residuals of tires are being used in different areas of civil construction, as a thin aggregate of concrete, revetment panels or in acoustics isolation. The application of the system of pre-molded plates, constructed with recyclable material has been used in popular buildings for most two decades in the city of Santa Cruz do Sul, RS. The construction system is executed in parte by prisoner workers, with the concrete plates being produced in the penitentiary, and through the self-construction of residencies with areas of 40 e 60m² by selfparticipation. However are still lacking scientific data on the constructive characteristics of these houses, as well as a after-occupational evaluation. Thus, the present Work presents data referring to the assays of soft and hard body, water resistant, thermal comfort and resistance to fire, as well as presents the base of the after-occupational evaluation of already existing houses for with new architectural proposals. The assays had shown that not all the analyzed parameters are inside the technical norms scales (NBRs). To take care of the necessities of the users of future habitation units, new architectural proposals for houses with 29,13m ², 29,28m ², 44,32m ² and 59,60m ² are presented using the constructive system with molded panels with addition of rubber residue.